Repetition as a structural and expressive resource: a study applied to musical composition - Levy Pacheco de Oliveira Neto (2022)
The current research aims to understand what are the cognitive consequences that arises from the use of repetitive elements in music to, posteriorly, consider how these elements might be manipulated by composers to optimize the transmission of their musical intensions to the audience. In order to do that, using as our main reference studies conduct by Elizabeth Margulis and David Huron, original pieces will be composed applying the analyzed techniques discovered in the theoretical part of this research.